2008
DOI: 10.1007/s10071-008-0151-6
|View full text |Cite
|
Sign up to set email alerts
|

Do chimpanzees learn reputation by observation? Evidence from direct and indirect experience with generous and selfish strangers

Abstract: Can chimpanzees learn the reputation of strangers indirectly by observation? Or are such stable behavioral attributions made exclusively by first-person interactions? To address this question, we let seven chimpanzees observe unfamiliar humans either consistently give (generous donor) or refuse to give (selfish donor) food to a familiar human recipient (Experiments 1 and 2) and a conspecific (Experiment 3). While chimpanzees did not initially prefer to beg for food from the generous donor (Experiment 1), after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 59 publications
6
99
1
1
Order By: Relevance
“…In Study 2, chimpanzees and orangutans, and in Study 3, human children also took into account experimenter actions toward others in forming reputations, which led them to choose a previously nice experimenter over a mean one in their own subsequent interactions with the experimenters. In sum, these studies demonstrate that at least some of our closest living relatives as well as human children have the ability to form direct and indirect reputation judgments, extending the findings with chimpanzees by Subiaul et al (2008) and Russell et al (2008) to orangutans. The reasons for the observed species differences are not entirely clear and should be subject to future research.…”
Section: Discussionsupporting
confidence: 68%
“…In Study 2, chimpanzees and orangutans, and in Study 3, human children also took into account experimenter actions toward others in forming reputations, which led them to choose a previously nice experimenter over a mean one in their own subsequent interactions with the experimenters. In sum, these studies demonstrate that at least some of our closest living relatives as well as human children have the ability to form direct and indirect reputation judgments, extending the findings with chimpanzees by Subiaul et al (2008) and Russell et al (2008) to orangutans. The reasons for the observed species differences are not entirely clear and should be subject to future research.…”
Section: Discussionsupporting
confidence: 68%
“…Although challenging, it is possible to study fairness in the laboratory removed from egocentric reactions. Experimental studies on reputation in chimpanzees indicates that these apes are able to form opinions about human experimenters from watching these experimenters interact with other chimpanzees (68). A fruitful line of inquiry would be to explore nonhuman primates' judgments of the equity of others' interactions.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…In an earlier study, chimpanzees spent more time near a human who shared food with another human than one who did not 15 ; this clearly suggests evaluation of a foraging opportunity. Another study reported that chimpanzees begged more from a generous person (who gave another food) than one who withheld food, but only after training 16 ; again this suggests that the apes were interested in getting more food. In the present study, both actors offered identical food to the monkeys; no foraging advantage followed from preferentially accepting food from either actor.…”
Section: Discussionmentioning
confidence: 99%